2019
DOI: 10.1039/c8py01520a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis of poly(lactic acid) block copolymers: overcoming the miscibility of the macroinitiator, monomer and catalyst under solvent-free conditions

Abstract: Efficient mixing and energy delivery by ball-milling promoted the lactide polymer growth from macroinitiators without the use of a solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…However, the relatively slow propagation rate of DBU-mediated trimethyl carbonate polymerization allowed for well-controlled chain lengths. The previous examples on mechanochemical poly(lactic acid) synthesis resulted in broader molecular weight distributions due to the fast propagation rate [1314].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the relatively slow propagation rate of DBU-mediated trimethyl carbonate polymerization allowed for well-controlled chain lengths. The previous examples on mechanochemical poly(lactic acid) synthesis resulted in broader molecular weight distributions due to the fast propagation rate [1314].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study on poly(lactic acid) synthesis, liquid-assisted grinding (LAG), the addition of a very small amount of a liquid, prevented chain-degradation from high impact collisions, and afforded PLA with over 100,000 g/mol. Thus, LAG was also tested in the PTMC synthesis [1314] with toluene and THF as liquids. A catalytic amount of liquid (10 or 20 µL to 100 mg TMC), however, failed to protect the poly(trimethylene carbonate) chain from mechanical degradation and similar molecular weights were obtained, regardless of LAG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Block co-polymerization of PLA with poly(ethylene glycol) (PEG) is another common technique used to enhance the biodegradability of polylactide [ 34 , 75 , 76 , 77 ]. A study revealed a solvent-free synthesis of a PLA–PEG block copolymer with enhanced biodegradability [ 78 ].…”
Section: Bio-based Materials For Packaging Applicationsmentioning
confidence: 99%
“…In the realm of polymer science, mechanochemistry has often been used as a tool for the controlled chain scission of macromolecules containing mechanophores . However, there are examples that describe the use of mechanochemistry to facilitate polymer synthesis . An idea that has been investigated to a lesser extent is the use of mechanochemistry to facilitate post‐polymerization modification reactions.…”
Section: Introductionmentioning
confidence: 99%